Produksi Padi Hibrida Intani 602 pada Berbagai Jarak Tanam: Sapta Kartika Sari - Sapta Kartika Sari (Sumber Penyuluhan Pertanian Indonesia, 2023)
The study aims to determine the planting distance and productivity of intani 602 hybrid rice on the land of the Suka Maju 15 farmer group leader, Tamanan subdistrict of Bondowoso. The study was conducted from November 2020 to March 2021. There are five planting distances studied, there are 20x20cm; 25x25cm; 30x30cm, jajar legowo planting pattern 2:1 and jajar legowo planting pattern 3:1. The results showed that the 20x20cm planting distance had the highest productivity for 602 intani hybrid rice.